A Tale of Encounters with Lia Rodrigues Cia. de Danças - Bianca Scliar Mancini (Concordia University – Montreal, Canadá) (Revista Brasileira de Estudos da Presença, 2013)
Lia Rodrigues  established her dance company in the neighbourhood of Alagados, in Rio de Janeiro. This article considers her presence at this urban zone as a procedure of presence, suggesting an attention to dance that precedes the process of choreographic composition, seen by the public. To investigate notions such as site, location and permanence and how they engender the work of her Company, the author follows three dancers through their urban trajectories. From that, a different notion of choreography arises, as well as a conception of dance that is initiated in the everyday trajectories, once one allows himself to cross the boundaries of social tension in order to execute, produce or enjoy a dance.